Impact of Glycemic Therapy on Myocardial Sympathetic Neuronal Integrity and Left Ventricular Function in Insulin Resistant Diabetic Rats: Serial Evaluation by 11C-meta-Hydroxyephedrine Positron Emission Tomography - Thackeray, James (Université d'Ottawa / University of Ottawa, 2012)
Diagnosis of diabetes mellitus, presence of hyperglycemia, and/or insulin resistance confer cardiovascular risk, particularly for diastolic dysfunction. Diabetes is associated with elevated myocardial norepinephrine (NE) content, enhanced sympathetic nervous system (SNS) activity, altered resting heart rate, and depressed heart rate variability. Positron emission tomography (PET) using the NE analogue [11C]meta-hydroxyephedrine ([11C]HED) provides an index of myocardial sympathetic neuronal integrity at the NE reuptake transporter (NET). The hypothesis of this project is that (i) hyperglycemia imparts heightened sympathetic tone and NE release, leading to abnormal sympathetic neuronal function in the hearts of diabetic rats, and (ii) these abnormalities may be reversed or prevented by treatments to normalize glycemia. Sprague Dawley rats were rendered insulin resistant by high fat feeding and diabetic by a single dose of streptozotocin (STZ). Diabetic rats were treated for 8 weeks with insulin, metformin or rosiglitazone, starting from either 1 week (prevention) or 8 weeks (reversal) after STZ administration. Sympathetic neuronal integrity was evaluated longitudinally by [11C]HED PET. Echocardiography measures of systolic and diastolic function were completed at serial timepoints. Plasma NE levels were evaluated serially and expression of NET and β-adrenoceptors were tested at the terminal endpoints. Diabetic rats exhibited a 52-57% reduction of [11C]HED standardized uptake value (SUV) at 8 weeks after STZ, with a parallel 2.5-fold elevation of plasma NE and a 17-20% reduction in cardiac NET expression. These findings were confirmed by ex vivo biodistribution studies. Transmitral pulse wave Doppler echocardiography established an extension of mitral valve deceleration time and elevated early to atrial velocity ratio, suggesting diastolic dysfunction. Subsequent treatment with insulin but not metformin restored glycemia, reduced plasma NE by 50%, normalized NET expression, and recovered [11C]HED SUV towards non-diabetic age-matched control. Diastolic dysfunction in these rats persisted. By contrast, early treatment with insulin, metformin, or rosiglitazone delayed the progression of diastolic dysfunction, but had no effect on elevated NE and reduced [11C]HED SUV in diabetic rats, potentially owing to a latent decrease in blood glucose. In conclusion, diabetes is associated with heightened circulating and tissue NE levels which can be effectively reversed by lowering glycemia with insulin. Noninvasive interrogation of sympathetic neuronal integrity using [11C]HED PET may have added value in the stratification of cardiovascular risk among diabetic patients and in determining the myocardial effects of glycemic therapy.
Keywords: positron emission tomography; diabetes; diastolic dysfunction; hydroxyephedrine; uptake-1; streptozotocin; image analysis